Death Sentencing on Perspective Law and Human Rights - Nur Alamsyah (International Conference of ASEAN Prespective and Policy (ICAP), 2018)
The issue of the application of capital punishment has become a circle by lawyers and human rights actors, both at the international level and in Indonesia itself until the implementation of the death penalty has led to the pro (the parties agree) and the counter (the party that leads). Although the death penalty is still enforced in the current regulation in Indonesia, to respond to the pros and cons of saying, later in the 2004 National Criminal Code Rules of Criminal Law, sex is no longer in the central prison. The criminal amendment may turn into a life-long parent and imprisonment for 20 years. Responding to the policy of the State of Indonesia in the context of the application of capital punishment, in the National Criminal Code Act of 2004. So it should be that the ASEAN countries follow the steps of the Indonesian State policy.